Deteksi Chrysanthemum B Carlavirus (CVB) pada Tanaman Krisan di Indonesia - TEMAJA, I G. R. M.; SUASTIKA, G.; HIDAYAT, SH.; KARTOSUWONDO, U. (AGRITROP; Vol. 26, No. 1 Maret 2007)
In a survey of chrysanthemum growing fields and greenhouses in Brastagi, Sumatera Utara; Cianjur, Jawa Barat; Malang, Jawa Timur; and Tabanan and Buleleng, Bali, some chrysanthemum cultivars were found showing mild leaf mottling, vein-clearing or vein banding of leaves and slight loss of flower quality. Out of 287 samples surveyed, the disease incidence ranged between 7.50% and 67.44%. Through DAS-ELISA, the saps extracted from diseased plant samples, 34.84% were found to be positively reacted with serum anti-CVB, but not with sera anti- CMV, -TSWV, -PVY and -TMV. The virus isolate was then designed as CVB Indonesian isolate. The virus was sap-transmissible to narrow host range. The virus induced systemic symptom on Nicotiana benthamiana, N. clevelandii, N. tabacum var. Burley, N. tabacum var. Havana; local necrotic lesion on Chenopodium amaranticolo, C. quinoa and both local and systemic symptom on Petunia hybrida.
Keywords: Chrysanthemum B carlavirus (CVB) Indonesian isolate, chrysanthemum, host range